2017
DOI: 10.7874/jao.2017.00206
|View full text |Cite
|
Sign up to set email alerts
|

Blind Sac Approach Using Silastic Block for Cochlear Implantation in Patients with Cholesteatoma

Abstract: Cochlear implant (CI) surgery in cholesteatoma is challenging because of the risk of residual or recurrent infection. Although CI could be done with subtotal petrosectomy in single or staged surgery, this surgery needed additional surgical procedures to obliterate the mastoid cavity. This paper describes a new surgical technique for CI surgery in cholesteatoma without external auditory canal closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…It also eliminates the need for life-long cavity care and water avoidance [Postelmans et al, 2009]. The procedure is feasible even in meatoplasty cases, and although some authors associate it with an esthetic disadvantage [Lyu and Park, 2017], we did not register any complaints in this regard, and observed that it can be even less obvious than the previous large opening [Szymański et al, 2016].…”
Section: Skull Base Lesions With Preservation Of the Cn And Cochleamentioning
confidence: 56%
See 3 more Smart Citations
“…It also eliminates the need for life-long cavity care and water avoidance [Postelmans et al, 2009]. The procedure is feasible even in meatoplasty cases, and although some authors associate it with an esthetic disadvantage [Lyu and Park, 2017], we did not register any complaints in this regard, and observed that it can be even less obvious than the previous large opening [Szymański et al, 2016].…”
Section: Skull Base Lesions With Preservation Of the Cn And Cochleamentioning
confidence: 56%
“…For CMOM cases, some authors advocate the use of simple tympanoplasty (TPL)/tympanomastoidectomy with CI, usually performed in 2 stages [Axon et al, 1995;Incesulu et al, 2004;Roehm and Gantz, 2006;Leung and Briggs, 2007;Hellingman and Dunnebier, 2009;Postelmans et al, 2009;Vincenti et al, 2014b;Yoo et al, 2014]. This approach may be hazardous due to the possibility of disease relapse [Vincenti et al, 2014b], or biofilm persistence [Lyu and Park, 2017] with consequent infection. Specifically, additional surgery is frequently required in such cases to control the disease [Barañano et al, 2013], including STP, MO, or EAC closure.…”
Section: Indications For Stp-ci Com/osteoradionecrosis Of the Temporamentioning
confidence: 99%
See 2 more Smart Citations